Pengaruh Ukuran Perusahaan, Pertumbuhan Aset, Profitabilitas dan Pajak Penghasilan Badan Terhadap Struktur Modal (Studi Kasus pada Perusahaan Kosmetik Yang Terdaftar Di BEI tahun 2013-2017) - Fipin Lastrian Dewi; Jeni Susyanti; Agus Salim (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
Abstract                The purpose of this study was to examine how the influence of firm size, asset growth, profitability and corporate income tax on the capital structure of cosmetic companies listed on the Indonesia Stock Exchange in 2013-2017.               The population in this study are all cosmetic companies listed on the Indonesia Stock Exchange. The sample selection uses a purposive sampling method. Based on the criteria obtained by 4 cosmetic companies listed on the Indonesia Stock Exchange in 2013-2017. The test method used is a multiple linear regression analysis test with hypothesis testing using the t test and F test.               The results of this study indicate that firm size, asset growth and profitability (ROE) have no effect on capital structure (DER). Whereas corporate income tax affects the capital structure. Simultaneously, the four independent variables influence the capital structure. Keywords: Firm Size, Asset Growth, Profitability and Corporate Income Tax.